2011
DOI: 10.1124/mol.111.076208
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization and Trafficking of μ-Opioid Receptors in Locus Ceruleus Neurons: Modulation by Kinases

Abstract: The phosphorylation of -opioid receptors (MOPRs) by G protein-coupled receptor kinases (GRKs), followed by arrestin binding, is thought to be a key pathway leading to desensitization and internalization. The present study used the combination of intracellular and whole-cell recordings from rats and mice, as well as live cell imaging of Flag-tagged MOPRs from mouse locus ceruleus neurons, to examine the role of protein kinases in acute desensitization and receptor trafficking. Inhibition of GRKs by using hepari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…These results are in line with previous findings demonstrating an important role of p38 MAPK activation in the induction of endocytotic receptor trafficking (Cavalli et al, 2001;Macé et al, 2005;McLaughlin et al, 2006;Vergarajauregui et al, 2006). It should be noted, however, that inhibition of p38 MAPK in mouse locus coeruleus neurons blocked neither desensitization nor endocytosis of MOR but did increase the rate of recovery from desensitization (Arttamangkul et al, 2012).…”
Section: G Involvement Of Other Kinases and Enzymessupporting
confidence: 81%
See 2 more Smart Citations
“…These results are in line with previous findings demonstrating an important role of p38 MAPK activation in the induction of endocytotic receptor trafficking (Cavalli et al, 2001;Macé et al, 2005;McLaughlin et al, 2006;Vergarajauregui et al, 2006). It should be noted, however, that inhibition of p38 MAPK in mouse locus coeruleus neurons blocked neither desensitization nor endocytosis of MOR but did increase the rate of recovery from desensitization (Arttamangkul et al, 2012).…”
Section: G Involvement Of Other Kinases and Enzymessupporting
confidence: 81%
“…However, blocking both processes nearly abolished MOR desensitization. Another study testing a combination of kinase inhibitors, including staurosporine and heparin, observed that acute desensitization to ME persisted, although there was a significant qualitative change in the pattern of receptor trafficking (Arttamangkul et al, 2012). The reason for persistence of desensitization in these studies when others examining the same neurons have observed greatly attenuated desensitization is not known.…”
Section: B G Protein Receptor Kinase Phosphorylation Arrestin Bindimentioning
confidence: 93%
See 1 more Smart Citation
“…2). Other approaches previously taken to inhibit GRKs include the broad-spectrum kinase inhibitor staurosporine (Arttamangkul et al, 2012), the PKC/GRK inhibitor 7,8,indol-10-yl]-4-(1-methyl-1H-indol-3-yl)-1H-pyrrole-2,5-dione hydrochloride] (Hull et al, 2010), "b-ARK-1 inhibitor" (Iino et al, 2002;Hull et al, 2010), and the antidepressant drug paroxetine (Thal et al, 2012;Homan et al, 2014b). However, none of these approaches combine the cell-permeability, potency, and selectivity profiles of Cmpd101.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, two studies have failed to provide evidence for any involvement of GRKs in MOPr desensitization. Neither heparin, a low-affinity GRK inhibitor, nor staurosporine, a nonselective kinase inhibitor, had any effect on methionine-enkephalin (Met-Enk)-induced MOPr desensitization in rat LC neurons (Arttamangkul et al, 2012). Also, using the GRK2as5 transgenic mouse, in which GRK2 has been mutated to allow chemical inhibition, it was observed that exposure to the inhibitor did not reduce Met-Enk-induced desensitization in LC neurons (Quillinan et al, 2011).…”
Section: Introductionmentioning
confidence: 98%